2017
DOI: 10.4183/aeb.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

Potential Advantage of Repaglinide Monotherapy in Glycemic Control in Patients with Type 2 Diabetes and Severe Renal Impairment

Abstract: Context. Oral anti-diabetic drugs (OADs) are leading option for treatment of type 2 diabetes (T2D). However, availability of OADs are limited in the presence of renal impairment (RI). Objective. In this study, we examined the efficacy of repaglinide, which is mainly metabolized and excreted via non-renal route, in patients with T2D and severe RI that consists mainly of chronic kidney disease (CKD) stage 4. Design, Subjects and Methods. This was an open label, single arm, interventional study by repaglinide mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Patients treated with sulphonylurea plus insulin, were shown to be at increased mortality risk when compared to metformininsulin combination (24). A new study showed that in addition to other well-known agents, repaglinide may also be a good candidate for achieving glycemic controls without causing hypoglycemia, especially in patients with renal impairment (25).…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with sulphonylurea plus insulin, were shown to be at increased mortality risk when compared to metformininsulin combination (24). A new study showed that in addition to other well-known agents, repaglinide may also be a good candidate for achieving glycemic controls without causing hypoglycemia, especially in patients with renal impairment (25).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of treatment strategies in type 2 diabetes is maintaining glycemic control to decrease the risk of complications. Dipeptidyl peptidase-4 (DPP-4) inhibitors are one of the current drug options for the treatment of type 2 diabetes (3)(4)(5). DPP-4 inhibitors are involved in the degradation of two endogenous incretin hormones glucagon-likepeptide 1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) and enhance active levels of these hormones and, in doing so, improve islet function as well as glycemic control in T2DM.…”
Section: Introductionmentioning
confidence: 99%